Effects of supplementation of limit-fed growing diets with either soybean meal or nonenzymatically browned soybean meal on steer performance - Coetzer, C.M.; Löest, C.A.; Bindel, D.J.; LaBrune, H.; Hunter, R.D.; Nutsch, T.A.; Higgins, James J.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seventy two individually fed Angus × Hereford steers (642 lb) were used to evaluate the effects of supplementing limit-fed, growing diets with either soybean meal (SBM) or nonenzymatically browned soybean meal (NSBM). Eight steers were allotted to a control diet composed of 39.1% high-moisture corn, 42% cottonseed hulls, 10.4% ground corn, 5% cane molasses 2.25% urea, and 1.5% vitamins and minerals (dry basis). The remaining steers were allotted to diets that derived 100, 80, 60, or 40% of their supplemental protein from SBM or 60, 45, 30, or 15% of their supplemental protein from NSBN. The balance of supplemental protein came from urea. All diets were formulated to contain 13.0% crude protein (dry basis). Steers were fed once daily for 80 days at 2.25% of BW. Average daily gain and efficiency did not differ (P>.05) between sources (ADG=1.932 + .103 × (% CP from SBM) + .097 × (% CP from NSBM); gain:feed=.140 + .0058 × (% CP from SBM) + .0051 × (% CP from NSBM)). The lack of response to NBSBM supplementation above that for SBM suggests that either degradable intake protein was limiting in the basal diet or a large proportion of the amino acids in the NSBM were unavailable due to overprocessing.
Keywords: Beef; Growing cattle; Nonenzymatically browned soybean meal; Undegraded intake protein